2021
DOI: 10.1093/ce/zkab021
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the residence’s intention to adopt solar photovoltaic technology: a case study from Klang Valley, Malaysia

Abstract: Recently, the Malaysian government has targeted to achieve the 20% renewable-energy goal by 2025. Despite the Malaysian government’s having taken initiatives in promoting the use of renewable energy for more than a decade, to date, more than three-quarters of the electricity supply in Peninsular Malaysia is generated from the burning of fossil fuels. Apparently, the development of renewable energy is still slow and in its infancy. The current study intends to identify the predictors (environmentalism, cost, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Policymakers and solar PV practitioners must execute several policies, according to Cheam et al [22] to increase the adoption of solar power. According to the current research, environmentally conscious users think that solar PV is more advantageous than users who are not as environmentally conscious.…”
Section: Recommendations To Integrate Rooftop Solar Pv In All the New...mentioning
confidence: 99%
See 1 more Smart Citation
“…Policymakers and solar PV practitioners must execute several policies, according to Cheam et al [22] to increase the adoption of solar power. According to the current research, environmentally conscious users think that solar PV is more advantageous than users who are not as environmentally conscious.…”
Section: Recommendations To Integrate Rooftop Solar Pv In All the New...mentioning
confidence: 99%
“…Because they lack knowledge and experience with solar PV, the locals think that installing solar PV will take a lot of work. As stressing the financial advantages alone will not be sufficient to encourage residents to embrace solar PV, the Malaysian energy commission and solar-market practitioners should step up their efforts to provide accurate information to residents [22]. To assist small and medium-sized businesses at various stages of the business cycle, various financial aids should be made available.…”
Section: Recommendations To Integrate Rooftop Solar Pv In All the New...mentioning
confidence: 99%
“…Murray (2012) in his study on intention to purchase solar panels found all three constructs of TPB to be the significant determinants of PI. In case of studies that have applied TAM, Ahmad et al (2017) in their study on public acceptance of solar PV technology found both the constructs of TAM: perceived ease of use (PEOU) and perceived utility to be the significant determinants of PI of solar PV technology, whereas Alam et al (2021) in their study on solar PV acceptance and Cheam, Lau, and Wei (2021) in their study on intention to adopt solar PV found PEOU not to be a significant determinant of PI of RETs.…”
Section: Introductionmentioning
confidence: 97%
“…Still, the issue of waste management continues to persist. More than 6 million tonnes of waste were generated from 2018, of which a quarter was produced in the Klang Valley alone [4]. It is estimated that 33% of construction waste directly resulted from the designer's inability to use waste minimization measures during the design phase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, The rapid rate of urbanization is responsible not only for the increased use of non-renewable resources but also for the development of significant amounts of C&D waste, as well as the associated environmental concern [11]. More than 6 million tonnes of waste were created in Malaysia, with a quarter of that made in the country's most prosperous region, the Klang Valley [4]. It is estimated that about 33% of construction waste results from designers' failure to use waste management measures (WMM) throughout the design process [12].…”
Section: Introductionmentioning
confidence: 99%